M-Library : Mengukur intelektual muslim dari kualitas perpustakaan - Taslim Batubara (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2019)
The writing of this scientific work aims to describe how the development of literacy in Muslim countries and how Islam develops with science and literacy. This paper is motivated by a sense of appreciation for Muslim scientists in the era of the glory of the Islamic dynasty and the desire to recall the advances in Islamic civilization in science, especially literacy as learning for the present generation. In addition, this article discusses how libraries and literacy play a major role and is the key to the development of ancient Islamic glory. This paper also tells how the Islamic library in its history also experienced a dark period. When Muslims were conquered by other nations such as Europeans, Tartars, and Indians many libraries were destroyed and their collections destroyed. The destruction of the library which later became the background of the breakup of the scientific chain, between the golden age of Islam and the era afterwards. It also makes the present reality, which makes Muslims become people who are left behind from other nations, for example, Europe, which is a symbol of intellectual progress in modern times.Keyword: Library, Literacy, Civilization of Islam.